PENERAPAN TATA KELOLA PEMERINTAHAN YANG BAIK DALAM PENGELOLAAN LEMBAGA PEMASYARAKATAN - Francois Geny Ritonga (Pusat Kajian Lembaga Pemasyarakatan, Fakultas Hukum, Universitas Kristen Indonesia, 2025)
Corrections are an integral part of the integrated criminal justice system administered by the government as part of the law enforcement process in the context of service, guidance, and counseling for social reintegration. After a person is found guilty by a court decision, the next step is to serve a prison sentence in a correctional institution. This is done based on the principles of legal protection and respect for human rights. However, there are currently dynamics occurring in correctional institutions, including overcapacity, inadequate prison personnel, and other issues that hinder the management and guidance of the rehabilitation process for inmates. With the concepts of state administrative law, regarding the need to reconceptualize and improve government administration, particularly the principles of proper governance, both at the central and regional levels, it is hoped that slowly but surely, this will change the structure, instrumentation, and orientation of government administration towards good governance.. The purpose of this study was to Implementation of Good Governance in the Management of Correctional Institutions. The method used is a normative legal research method.